DUALITAS LITERATUR YANG TERCERMIN DALAM CERITA PAN BALANG TAMAK - Cristiana, Olga (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The folk tale of Pan Balang Tamak is one of the renowned regional literatures from Bali, known for its character Pan Balang Tamak. This study aims to analyze the Balinese folk tale of Pan Balang Tamak as a literary work with duality. Moreover, the focus of the research lies in analyzing the paradigms reflected in the story of Pan Balang Tamak. This research provides a new perspective on the interpretation of the Pan Balang Tamak story in relation to the global societal conditions. Based on the analysis results, the story of Pan Balang Tamak reflects literary duality, where it can be interpreted as satire, a sharp critique of certain conditions or policies, and also as a hikayat, a narrative containing deeper moral or messages. The main character, Pan Balang Tamak, can be seen with striking duality. On one side, he can be perceived as a character who is clever and possesses certain wisdom in his actions. On the other side, his cunningness may give a less positive impression. The thoughts held by the main character reflects the social exchange paradigm and the social norms paradigm within the traditional setting of the story. Certainly, these findings are expected to contribute to a new perspective on regional literature related to the current globalization conditions.